Periodical assessment of genitourinary and gastrointestinal toxicity in patients who underwent prostate low-dose-rate brachytherapy - Tanaka Nobumichi (Radiation Oncology, 2013)
Abstract Background To compare the periodical incidence rates of genitourinary (GU) and gastrointestinal (GI) toxicity in patients who underwent prostate low-dose-rate brachytherapy between the monotherapy group (seed implantation alone) and the boost group (in combination with external beam radiation therapy (EBRT)). Methods A total of 218 patients with a median follow-up of 42.5 months were enrolled. The patients were divided into 2 groups by treatment modality, namely, the monotherapy group (155 patients) and the boost group (63 patients). The periodical incidence rates of GU and GI toxicity were separately evaluated and compared between the monotherapy group and the boost group using the National Cancer Institute - Common Terminology Criteria for Adverse Events, version 3.0. To elucidate an independent factor among clinical and postdosimetric parameters to predict grade 2 or higher GU and GI toxicity in the acute and late phases, univariate and multivariate logistic regression analyses were carried out. Results Of all patients, 78.0% showed acute GU toxicity, and 7.8% showed acute GI toxicity, while 63.8% showed late GU toxicity, and 21.1% showed late GI toxicity. The incidence rates of late GU and GI toxicity were significantly higher in the boost group. Multivariate analysis showed that the International Prostate Symptom Score (IPSS) before seed implantation was a significant parameter to predict acute GU toxicity, while there were no significant predictive parameters for acute GI toxicity. On the other hand, combination with EBRT was a significant predictive parameter for late GU toxicity, and rectal volume (mL) receiving 100% of the prescribed dose (R100) was a significant predictive parameter for late GI toxicity. Conclusions The boost group showed higher incidence rates of both GU and GI toxicity. Higher IPSS before seed implantation, combination with EBRT and a higher R100 were significant predictors for acute GU, late GU and late GI toxicity.